Nilai-nilai Intelektual dalam Mite Pangeran Samudro di Gunung Kemukus Sragen Jawa Tengah (Sutasoma : Jurnal Sastra Jawa, 2022)
Not many people know about the causal history of phenomenology other than tautologies, which raises more questions than helps find such answers. One of these phenomena is the existence of the myth of Prince Samudro on Mount Kemukus, Sragen. To find out the intellectual values or messages in the myth of Prince Samudro, the method used is the Levi Strauss structural approach and a combination of historical explanation, Verstehen method, conflict theory, and Lyotard’s critique of thought. Research on the myth covers several aspects of life, including intellectual mythology, moral values, norms, teachings, philosophy, mandate, functions, and benefits. In this study, the researcher takes one of the aspects above, namely the intellectual values in the myth of Prince Samudro on Mount Kemukus. This study finds that in the mythical story of Prince Samudro on Mount Kemukus, there is a historical mystery that invites pros and cons. On the one hand, pilgrimage procedures must be done in earnest. But, on the other hand, have to do sex ritual. The story is made subtly, full of symbols or often called gedhong literature. Keywords: myth; structural approach; intellectual value